Symptomatology of Sigatoka leaf spot disease in banana landraces and identification of its pathogen as Mycosphaerella eumusae - Milsha George; K. Anita Cherian; Deepu Mathew (Journal of the Saudi Society of Agricultural Sciences)
Mycosphaerella musicola, M. fijiensis and M. eumusae are known to cause banana yellow Sigatoka, black Sigatoka and Eumusae leaf spot diseases respectively. However, differentiating the causative species has been challenging and the responses of banana landraces to this pathogen were little known. Purposive sampling surveys were conducted in different agro-climatic zones of Kerala state, India, to collect the leaf samples with Sigatoka leaf spot-like symptoms, to document the symptom expression on different landraces and to confirm the identity of the pathogen at species level. Fields surveyed during the post-monsoon period had 100% disease incidence with highest per cent disease severity of 43.90% in nine-month old cv. Palayankodan, while lowest PDS of 3.33% was observed in three-month old cv. Njalipoovan, during a pre-monsoon survey. Initial symptoms were small brown streaks, later developing into oval or elliptical brown spots with greyish centre and subsequently coalescing for leaf necrosis. Symptoms in different landraces varied across the zones. Sequencing and analysis of the ITS region from 50 isolates collected during the survey showed 99–100% homology with M. eumusae. Phylogenetic analyses further proved the species identity of the local isolates. Comparing the ITS barcodes of the three species of Mycosphaerella along with the local isolates confirmed that the pathogen inciting Sigatoka leaf spot in Kerala state, India, is Mycosphaerella eumusae.